2020
DOI: 10.3390/pathogens9040287
|View full text |Cite
|
Sign up to set email alerts
|

The Complex Relationship between HTLV-1 and Nonsense-Mediated mRNA Decay (NMD)

Abstract: Before the establishment of an adaptive immune response, retroviruses can be targeted by several cellular host factors at different stages of the viral replication cycle. This intrinsic immunity relies on a large diversity of antiviral processes. In the case of HTLV-1 infection, these active innate host defense mechanisms are debated. Among these mechanisms, we focused on an RNA decay pathway called nonsense-mediated mRNA decay (NMD), which can target multiple viral RNAs, including HTLV-1 unspliced RNA, as has… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 130 publications
0
9
0
Order By: Relevance
“…Co-IP experiments against Tax from HTLV-1-infected cells, identified INT6 (one of the thirteen eIF3 subunits) and UPF1 as interaction partners [ 156 ]. NMD inhibition by Tax depends on its interaction with INT6, as Tax mutants that are unable to bind to INT6 were found to have no effect on NMD [ 157 , 158 ], suggesting an involvement of eIF3 in NMD of mRNAs with long 3′-UTRs. In addition, Tax interacts with the helicase domain of UPF1 and reduces its RNA-binding affinity by blocking the RNA entry site.…”
Section: Viral Evasion Of Nmdmentioning
confidence: 99%
See 1 more Smart Citation
“…Co-IP experiments against Tax from HTLV-1-infected cells, identified INT6 (one of the thirteen eIF3 subunits) and UPF1 as interaction partners [ 156 ]. NMD inhibition by Tax depends on its interaction with INT6, as Tax mutants that are unable to bind to INT6 were found to have no effect on NMD [ 157 , 158 ], suggesting an involvement of eIF3 in NMD of mRNAs with long 3′-UTRs. In addition, Tax interacts with the helicase domain of UPF1 and reduces its RNA-binding affinity by blocking the RNA entry site.…”
Section: Viral Evasion Of Nmdmentioning
confidence: 99%
“…In addition, Tax interacts with the helicase domain of UPF1 and reduces its RNA-binding affinity by blocking the RNA entry site. Using single-molecule techniques, Tax was also shown to interact with RNA-bound UPF1, blocking its ATPase and helicase activities leading to the dissociation of UPF1 from the mRNA [ 156 , 158 ]. Taken together, Tax appears to inhibit NMD by binding UPF1 and INT6 and interfering with their interaction [ 156 ].…”
Section: Viral Evasion Of Nmdmentioning
confidence: 99%
“…Unspliced HTLV-1 mRNA, like the unspliced mRNA of other single-stranded positive-sense RNA members of the Retroviridae family, harbors an unusually long (~4-kilobase) 3'UTR that likely causes its observed targeting by NMD (Prochasson et al 2020). To counteract NMD, HTLV-1 has taken minimally a two-pronged approach by producing the trans-acting factors Rex and Tax.…”
Section: Viral-escape Strategies In Trans: Nmd Inhibitionmentioning
confidence: 99%
“…It has also been reported that Tax inhibits NMD via interaction with Upf1 and eIF3E/INT6 [33,34]. Recently, Prochasson et al elegantly reviewed the relationship between HTLV-1 and host NMD [35]. However, the offense and defense between HTLV-1 and NMD are complex and it remains unclear how HTLV-1 evades this powerful host mRNA quality control mechanism.…”
Section: Introductionmentioning
confidence: 99%